From ‘Ratcatraz Prison’ to ‘Penjara Pudutikus’: lexical creativity in children’s literature and its translation into Malay - Atikah Zabir,; Haslina Haroon, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Lexical creativity is one of the ways through which authors of children’s literature shape their stories, entertain children and build their identity and style. In spite of their uniqueness, creative lexical items are often replaced with more common words in translation, a phenomenon described through the law of growing standardisation hypothesis. In view of the importance of creative lexical items in children’s literature, there is a need to explore how creativity is transferred in the process of translation. This study is carried out to examine the translation of lexical creativity in children’s literature from English to Malay. More specifically, the aims of the study are to identify the types of creative lexical items in children’s literature in English and to determine how translators transfer creativity from English into Malay. The study also aims to determine whether the hypothesis of the law of growing standardisation applies in the context of the translation of children’s literature from English into Malay. The study employs a corpus-based model for research on the translation of creative lexical items. Corpus analysis tools are used to identify different forms of creative lexical items and to identify the translations for these items. Based on the analysis, five types of creative lexical items are identified; many, however, are replaced with common words when translated into Malay, resulting in the loss of unique features of the original works. It is, however, also found that translators compensate for some of these losses by introducing other elements in the Malay translations.